PENGARUH DIAMETER DAN KETEBALAN PASIR PADA SARINGAN TERHADAP TOTAL SOLID DALAM AIR - Anwar Fuadi, Anwar Fuadi (Jurnal Sains dan Teknologi Reaksi, 2003)
Water is the main need for the human beings. One of the criteria of safe to be consumed where the total undissolved solids must be suitable with maximum standard that is retained. One of ways to reduce the total undissolved solid in the water can be done with gravity sand filter. Water which flows through packed bed (sand) and suspended solid will be blocked up by the sand and suspended solid will be blocked up by the sand and clarified liquid at the bottom. The main purpose of this research is to know the influence between diameter and bed (sand) thickness on the total solids decreasing process, and compared which the diameter and thickness that give the total solids decreasing better. The statistic analysis result showed that the solid decreasing was influenced by diameter and bed layer thickness.